A Plastic Surgeons Guide to the Temporomandibular Joint: Part III, Treatment. Issue 2 (June 2023) - Mantilla-Rivas, Esperanza; Crowder, Hannah R.; Nasser, Jacob S.; Manrique, Monica; Ibelli, Taylor J.; Buller, Mitchell; Oh, Albert K.; Rottgers, S. Alex; Taub, Peter J.; Wolfswinkel, Erik M.; Marrazzo, Jason M.; Rogers, Gary F.
The temporomandibular joint (TMJ) has a complex and unique anatomy. When disarranged, it may produce a constellation of symptoms and dysfunction, leading to morbidity. The causes of TMJ dysfunction are numerous but often present with similar clinical signs and symptoms. In this series, we included a review of normal anatomy and a review of the pathophysiology with assessment of the most common TMJ dysfunctions, including myofascial pain, internal derangements of the articular disk, osteoarthrosis, among others. The authors present the last of a 3-part educational series on the TMJ, addressing treatment strategies for these disorders.